An integrated chemical-biological study using caged mussels (Mytilus trossulus) along a pollution gradient in the Archipelago Sea (SW Finland, Baltic Sea). (August 2016) - Lehtonen, Kari K.; Turja, Raisa; Budzinski, Hélène; Devier, Marie-Hélène
Abstract: Mussels ( Mytilus trossulus ) were caged along a known pollution gradient in the inner Archipelago Sea (northern Baltic Sea) and retrieved after 71 and 121 d for the measurement of selected chemical contaminants in tissues and biological endpoints including biochemical biomarkers and growth. Additional samples were collected during the growth season from a native mussel population at an alleged reference site. Elevated concentrations of numerous contaminants (e.g., PAH) were observed in spring, apparently due to the loss of tissue mass during the winter, while also the levels of many biomarkers (e.g., glutathione S -transferase activity) were elevated. Spatial and temporal changes in the accumulation of contaminants and biological parameters were observed with some of them (e.g., growth) linked to seasonal changes in environmental factors. The results underline the importance of understanding the effects of seasonal natural factors on the growth dynamics and general condition of mussels when assessing tissue concentrations of contaminants and biological effects. Highlights: Marked tissue loss during winter results in high contaminant levels in spring. High tissue contaminant levels in spring concur with elevated biomarker levels. Seasonality in growth and condition affect levels of contaminants and biomarkers. Variability in chemical and biological parameters along the pollution gradient. Mussel caging is an effective method in pollution biomonitoring in the Baltic Sea.